2014
DOI: 10.1007/82_2014_390
|View full text |Cite
|
Sign up to set email alerts
|

Transmission in the Guinea Pig Model

Abstract: The ability of an influenza virus to transmit efficiently from human-to-human is a major factor in determining the epidemiological impact of that strain. The use of a relevant animal model to identify viral determinants of transmission, as well as host and environmental factors affecting transmission efficiency, is therefore critical for public health. The characterization of newly emerging influenza viruses in terms of their potential to transmit in a mammalian host is furthermore an important part of pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 91 publications
0
44
0
Order By: Relevance
“…This working model will be tested in our future experiment. Transmission experiments using influenza types A and B in various animal models also showed higher efficiency in transmission by the contact route than by the aerosol route (14). Swine FLUDV was also reported to transmit by contact in pigs and ferrets (7).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This working model will be tested in our future experiment. Transmission experiments using influenza types A and B in various animal models also showed higher efficiency in transmission by the contact route than by the aerosol route (14). Swine FLUDV was also reported to transmit by contact in pigs and ferrets (7).…”
Section: Discussionmentioning
confidence: 96%
“…Our study was based on the following considerations. First, guinea pig has been used extensively as an alternate mammalian animal model for studying the pathogenesis of many influenza viruses, including FLUBV (13)(14)(15). Second, this animal model was susceptible to infections by influenza A virus subtypes and demonstrated virus replication in lungs.…”
Section: Influenza D Virus (Fludv) Is a Novel Emerging Pathogen With mentioning
confidence: 99%
“…Increased transmission of the first dominant influenza strain may later lead to development of sufficient immunity among the population, which in turn will stop or decrease the spread of the virus. Consequently increased activity of co-circulating strains [36, 37] occurs.…”
Section: Discussionmentioning
confidence: 99%
“…His laboratory went on to demonstrate that commercially available, outbred Hartley strain guinea pigs could be productively infected with an unadapted human isolate by intranasal inoculation and could transmit the virus both to uninfected cage-mates and to naïve guinea pigs in cages up to 91 cm (3 feet) away [50]. Inbred Strain 2 and Strain 13 guinea pigs were similarly susceptible to infection with human influenza virus strains and could transmit virus to susceptible partner animals; however, inbred colonies are privately held and are less readily procured than are commercially bred Hartley guinea pigs [50, 52, 66]. Further research by the Palese group has demonstrated the presence of antibodies to human influenza viruses in livestock guinea pigs raised in three different regions of Ecuador, where guinea pig meat ( cuy ) is part of the traditional Andean cuisine [67].…”
Section: Guinea Pig Modeling Of Influenza Virus Transmission: a Histomentioning
confidence: 99%